MENINGKATKAN PENGUASAAN KOSAKATA MELALUI FINDING WORDS GAME SISWA KELAS DELAPAN DI SMPN 1 SUMBERGEMPOL TULUNGAGUNG TAHUN AKADEMIK 2015/2016 - Purwasih, Galuh Dwi (Jurnal al Hikmah, 2016)
This study design using Action Research (PTK), so the researchers are using Actional hypothesis. The hypothesis of this study can be stated as follows: "If the Word Game Finding applied to the eighth graders, makaakan improve their vocabulary mastery at SMPN 1 Sumbergempol academic year 2015/2016. The procedure of this study consists of five steps, preliminary studies, planning the action, observing the action, carrying out the action, and reflect the action. This research was conducted in two cycles to evaluate the ability of students vocabulary mastery. Data collected from: observation, field notes, interviews, questionnaires, and vocabulary test. Observation and field notes describe the process of implementation of the find word games. Interviews and questionnaires were used to evaluate the response of the students about the find method of word games to improve their mastery of vocabulary. vocabulary test is required to evaluate the ability of students vocabulary. This research was conducted in SMP Negeri 1 Sumbergempol. The subjects of this study were 38 students from the eighth grade E. success of 85% among all members of the students in the classroom. And the average value was 75. The results showed that the application of the method of word find games can improve students ability Vocabulaary. This increase is marked by the increasing success of the class vocabulary test administered at the end of each cycle. In a preliminary test, there are 10% of 38 students in the class passed the test. In the first cycle, there was 50% of 38 students in the graduating class vocabulary test cycle I. In the second cycle, there are 90% of the students passed the test cycle vocabulary II. The results of the student questionnaire showed that students eager to follow the activities and they are keen to use the find words gamek method for increasing vocabulary through word finding game. This means that the find method of word games can improve students vocabulary mastery in the eighth year, and there are points that can be inferred from this study.